Typology and Visual Analysis of Seyed Ali Akbar Golestaneh's Shikasta Script Writings - Mehran Behzadi; Seyyed Reza Hoseini; Amin Iranpour; Mohammad Sadegh Mirzaabolghasemi (پیکره)
Introduction: Seyed Ali Akbar Golestaneh is one of the prominent Shikasta scriptwriters whose works and status in the history of calligraphy have been the focus of calligraphy artists and researchers. Considering the importance of this Shikasta-Nastaliq calligrapher's position, identifying his works' artistic features and styles still seems necessary. Accordingly, the present research deals with the typology and visual analysis of Seyed Ali Akbar Golestaneh's Shikasta script works in terms of good layout (ḥosn-e ważʿ) and composition (tarkīb). Identifying the typological and stylistic features of Seyed Ali Akbar Golestaneh's Shikasta script works with an emphasis on good layout (ḥosn-e ważʿ) and composition (tarkīb) is the primary goal of this research.Research Method: The data for the present research has been collected using a library-based method and relying on the original images of the works in Murraqqaꞌs as well as calligraphic and printed pieces. The analysis in this research is conducted qualitatively using a visual analysis method based on the components of visual analysis of visual works and specialized concepts related to the principles and rules of calligraphy (observing Shikasta-Nastaliq script).Findings: Golestaneh's Shikasta script works include two types of prose and verse texts. Multiple baselines or seatings (korsī) and overlaying (mounted letters and words) are the characteristics of his Linear-script writing (Satr Nevisi), which are directly related to the length of the line. Examples of Golestaneh's Shikata script writings, including a smaller number of his works, include pieces in Khafi Dang (small), executed in a double-diagonal script (Chalipa) and multi-direction form. From the beauty of disposition (ḥosn-e ważʿ) perspective, the trend towards the horizontal frame and seating (korsī), at the same time, multiple sub-seatings in most of the works, as well as multi-direction writing in some works, are the characteristics of Golestaneh's Shikasta Scriptwriting.Conclusion: The dominant aspect of Golestaneh's works is the type of linear script (Satr Nevisi) and the tendency to write in Jali script. The inclination towards horizontal frames and seating (korsī) and, at the same time, multiple sub-seating are the dominant characteristics of his works. Two-Dang writing (Khafi and Jali) can also be seen in several of Golestaneh's works. Regarding simple-letter composition, the features of complex writing, the system of composition and arrangement of elongations (Mads), the tendency to alliance of circular and curved forms in both horizontal and stepped ways, and the composition of micro-elements (including repetition of similar and aligned movements, tangency, intrusion, and merging of letters with each other) in Golestaneh's works can be expressed.